University as a Champion of Sustainable Development: Objectives, Approaches and Practice - E. A. Loktionova; D. I. Khlebovich (Вестник Российского экономического университета имени Г. В. Плеханова)
The article reviews the objectives connected with present day university functioning within the frames of the UN global agenda, i.e. to ensure sustainable development. The academic community is interested mainly in finding the answer to the question about new approaches to conducting education, research and administrative functions of the university. University is considered as an influential institution, which promotes innovation and train future specialists to make responsible decisions. Values and goals of sustainable development affect universities, thus the aim of the article is to show in what way university can pursue ideology of system changes through realization of its education mission. The UN initiative ‘Responsible Managerial Education’ (RME) is seen as an approach to promoting sustainable development in universities and to designing new education programs. It is pointed out that by realizing principles of responsible managerial education in master course universities can develop practices contributing to goal attainment in the field of sustainable development. As a driver for RME realization the Englishlanguage master course program ‘Sustainable Management' was advanced, which relies on orientation to goals of sustainable development and principles of responsible managerial education. The authors put forward a concept of the program for Russian universities that includes methodological approaches to its construction, rough curriculum and expected outcomes. It is shown that system efforts aimed at attaining goals of sustainable management through responsible managerial education shall be continued by using the proposed solutions and searching for new ones. The authors identify spheres of university functioning that require serious reforms. Conclusions are drawn about new discourses in the field higher education connected with comprehending the involvement of universities in initiatives of sustainable development.